2006
DOI: 10.1677/joe.1.06615
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum sanctum leaf extracts stimulate insulin secretion from perfused pancreas, isolated islets and clonal pancreatic β-cells

Abstract: Ocimum sanctum leaves have previously been reported to reduce blood glucose when administered to rats and humans with diabetes. In the present study, the effects of ethanol extract and five partition fractions of O. sanctum leaves were studied on insulin secretion together with an evaluation of their mechanisms of action. The ethanol extract and each of the aqueous, butanol and ethylacetate fractions stimulated insulin secretion from perfused rat pancreas, isolated rat islets and a clonal rat -cell line in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 28 publications
(26 reference statements)
2
81
1
Order By: Relevance
“…It regulate carbohydrate metabolism in STZ induced diabetes in rats [20]. The glucose lowering effects of O. sanctum leaf was found to be mediated through its insulin secretagogues effects on pancreas [21]. The phytochemical studies showed that O. sanctum contains a variety of medicinal-chemical compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It regulate carbohydrate metabolism in STZ induced diabetes in rats [20]. The glucose lowering effects of O. sanctum leaf was found to be mediated through its insulin secretagogues effects on pancreas [21]. The phytochemical studies showed that O. sanctum contains a variety of medicinal-chemical compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence was estimated at 2.8% in 2000 (171 million people) [1], 382 million people in 2013 and estimated to reach 55% (592 million people) by 2035 if no concerted effort is done to eliminate the progression [2]. The reasons for this include changes in lifestyle associated with urbanization, modernization [3], growth of aged population, increasing trends towards obesity, unhealthy diet, sedentary lifestyles [4], with hypertension, coronary heart disease, stroke, genetics and various forms of cancer among the factors contributing to the estimated rise [5,6]. The main challenge in treating DM is that it is no longer treated as a single disorder, but as a collection of conditions with a common result of hyperglycemia and resultant widespread multi-organ complications, that may occur in either two common forms, Type I (insulin-dependent diabetes mellitus; IDDM) and Type II (non-insulin-dependent diabetes mellitus; NIDDM) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ocimum sanctum Linn. (Labiatae), commonly known as holy basil, is an herbaceous plant found throughout the South Asian region [10]. The oil of Ocimum sanctum possesses antibacterial, antifungal, antioxidant and radioprotective properties [11].…”
Section: Introductionmentioning
confidence: 99%